2022
DOI: 10.1186/s13018-022-03281-4
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous versus staged bilateral total hip arthroplasty: a systematic review and meta-analysis

Abstract: Background Total hip arthroplasty is a common orthopedic surgery for treating primary or secondary hip osteoarthritis. Bilateral total hip replacement could be performed in a single stage or two separate stages. Each surgical procedure's reliability, safety, and complications have been reported controversially. This study aimed to review the current evidence regarding the outcomes of simultaneous and staged bilateral total hip arthroplasty. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 81 publications
0
11
1
2
Order By: Relevance
“…Our study shows good medium-term patient-reported functional outcomes following simultaneous bilateral THR at a mean follow-up of 7.8 years. Radiological assessment did not show any worse LLD when compared to standard mean values of 3-17 mm after THR described in a literature review [16], thus negating our initial hypothesis. In our series, parameters such as intra-operative blood loss, mean hospital stay, and postoperative complications, such as thromboembolic events, showed an improvement over existing studies, although this should be taken in the context of our series being low volume.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Our study shows good medium-term patient-reported functional outcomes following simultaneous bilateral THR at a mean follow-up of 7.8 years. Radiological assessment did not show any worse LLD when compared to standard mean values of 3-17 mm after THR described in a literature review [16], thus negating our initial hypothesis. In our series, parameters such as intra-operative blood loss, mean hospital stay, and postoperative complications, such as thromboembolic events, showed an improvement over existing studies, although this should be taken in the context of our series being low volume.…”
Section: Discussioncontrasting
confidence: 55%
“…The practice of simultaneous bilateral THR was shown in earlier studies to be associated with an increase in complications such as deep vein thrombosis (DVT), prosthetic joint infection (PJI), heterotrophic ossification (HO), and decreased gait stability [9][10][11]. Recent literature has shown equivalent rates of mortality and PJI when compared to staged procedures, but increased rates of pulmonary embolism (PE) [16]. The advocates of simultaneous bilateral THR argue that it is cost-effective by reducing the overall length of hospital stay and anaesthetic and surgical time without any significant change in functional outcome as compared to a staged procedure [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…The comparative studies of simultaneous total joint arthroplasty involving two joints (either both knees, both hips, or an ipsilateral combination of hip and knee during a single anaesthesia session) versus staged procedures performed under separate anaesthesia sessions have been extensively researched 2 5–11. Simultaneous bilateral TKA initially had higher complication rates than staged bilateral or unilateral TKA.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, simultaneous bilateral THA results in fewer complications, including reduced deep vein thrombosis and systemic, local, and pulmonary complications. Additionally, it offers cost savings due to shorter hospital stays and less blood loss compared with staged THA 11. However, it is advisable to avoid performing multiple joint replacements during a single anaesthetic session in elderly patients, those with multiple comorbidities (especially with an American Society of Anesthesiologist’s physical status classification >3), patients who are not mentally prepared for such procedures, and in healthcare centres with low surgical volumes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation